Commissioning and analysis of new desulfurization wastewater treatment system in a coal-fired power plant - LIU Guidong; HU Yangyang; WANG Jing; CHEN Yang; WANG Zhiyong; DANG Yulu; XU Hao (Gongye shui chuli)
In a desulfurization wastewater renovation project of a coal-fired power plant in Shandong Province, the original triple-tank process was replaced by integrated high efficiency clarification process to treat the desulfurization wastewater, with suspended solids of 13 650 mg/L, CODCr of 350 mg/L and heavy metal ion concentration exceeding the standard. The basic chemical dosage could be determined by laboratory test. By on-site equipment joint adjustment, the operating parameters could be optimized and equipment damage rate could be reduced. After 168 h commissioning and running, the new process of desulfurization wastewater system was stable and effective. The effluent SS was 1.5 mg/L, CODCr was 132.2 mg/L, total lead, total cadmium, total mercury, total chromium, and total zinc were 0.14, 0.01, 0.01, 1.04, and 1.24 mg/L, respectively. The effluent quality could meet the relevant indicators of the Discharge Standard of Wastewater from Limestone-Gypsum Flue Gas Desulfurization System in Fossil Fuel Power Plants (DL/T 997-2020). Compared with the original triple-tank process in power plants, the integrated high-efficiency clarification process not only significantly improved water quality, but also reduced annual operating costs from over 1 million yuan to over 0.5 million yuan, with significant economic effects.